Intervention effectiveness towards improvement on knowledge, health beliefs and anticipated help-seeking for ovarian cancer among university non-academic staff in Malaysia - Almahdi, Najat Milad (2018)
Ovarian cancer (OC) is one of the deadliest gynecological cancer because of late detection of it. Early detection could be promoted by increasing knowledge, and minimizing barriers and improving time of seeking medical help for ovarian cancer symptoms. Previous studies showed low ovarian cancer awareness among working Malaysian women. The main objective of this study was to develop, implement and evaluate the effectiveness of an educational intervention to improve ovarian cancer knowledge, health beliefs, perceived barriers, and anticipated help-seeking among female non-academic staff in Universiti Putra Malaysia (UPM). This is a randomized controlled trial (RCT), considered in three phases. Phase I was a cross sectional study aimed to obtain current data on the knowledge and attitude related to OC among female non-academic staff in UPM. Data was collected from 366 participants. Response rate of 91.5%. About 96.4% of them were Malay, with mean age of 34 years (SD 7.8). A low knowledge was reported by 46.5% of participant which was predicted by age (P=0.01) and having heard or read about OC (P < 0.001). Half of participants showed negative attitude related to OC, which were predicted by marital status (P<0.001), education level (P=0.02), and having heard or read about OC (P=0.02). In Phase II, educational module was developed according to the Health Belief Model (HBM) and validated. The module composed of educational videos, leaflet, and ovarian cancer symptoms checklist diary. In Phase III (RCT), multi-stage random sampling was used to select 305 of female nonacademic staff who were randomly allocated into study groups (157 in the intervention group vs. 148 in the control group at baseline). The response rate were 73.6%. Data was collected at baseline, immediately, and 3 months after intervention using a validated online questionnaire that adapted from Ovarian Cancer Awareness Measures (Ovarian CAM). There was no significant differences in sociodemographic characteristics between intervention and control group. The mean age of participants was 37.8 years (SD 8.1), and the majority were Malay (96.7%). In the intervention group, the mean scores of anticipated help-seeking, knowledge, and confidence in symptom detection had increased significantly from baseline to immediately, and 3 months after intervention [5.9 (SD 2.6), 6.7 (SD 2.9), 8.8 (SD 1.4), p< 0.001], [5.2 (SD 3.3), 12.3 (SD 2.7), 11.17 (SD 2.5), p<0.001], and [2.19 (SD 1.0), 2.5 (SD 0.91), 2.6 (SD 1.0), p=0.001] respectively. Similarly, the mean scores of the three types of perceived barriers had increased significantly after the intervention at baseline, immediately and 3 months which include: emotional barrier [3.14 (SD 0.9), 1.19 (SD 0.9),1.69 (SD 0.9), p<0.001], practical barrier [1.93 (SD 0.9), 1.79 (SD 0.9), 0.73 (SD 0.8), p<0.001], and service barrier [1.73 (SD 0.8), 1.64 (SD 0.8), 1.62 (SD 0.8), p<0.001]. The mean score of the perceived benefits shows a significant increase after the intervention at baseline, immediately and 3 months [10.9 (SD 2.5), 11.3 (SD 2.5), 11.5 (SD 2.7), p<0.001]. However, the perceived susceptibility mean score showed non-significant increase at the three points of assessments of study [11.8 (SD 2.8) 12.5 (SD 3.6), 12.7 (SD 3.7), p=0.08]. The control group showed no significant changes in all measured aspects. These results provide evidence for the effectiveness of the electronic-based educational intervention in increasing ovarian cancer knowledge, and anticipated help-seeking for ovarian cancer symptoms among Malaysian non-academic staff at UPM. This study suggests that knowledge on ovarian cancer can improve anticipated seeking help behavior for short term duration. In addition, long term effects need to be addressed for promoting ovarian cancer early detection among Malaysian women.